Sebastian Scharff, Hellenistic athletes: agonistic cultures and self-presentation. - Stavrou, Dorothea (Journal of Greek Archaeology, 2025)
In his introduction, Scharff starts with a brief overview of previous scholarship. He deals with how scholars have moved on from the traditional view that the Hellenistic period saw a decline in agonistic life to a new outlook resting on new evidence and fresh thought that draws on sociological, political, historical, archaeological and linguistic perspectives. In contrast to previous studies, Scharff’s focus is upon the victorious competitors (in both athletic and equestrian contests) and on their self-representation. Having analysed the broader context and listing the factors that inform his study, Scharff gives an account of his methodology, stressing in particular that he focusses on victor epigrams as a key element in the representation of athletic glory. This approach will reveal, he believes, the existence of a direct or indirect ‘agonistic discourse’ among athletes, cities, regions, kings, courtiers and prominent citizens. Such a discourse, says Scharff, is naturally influenced by current circumstances and how athletes wish their victory to be perceived.